Discovery of 2-(4-Acrylamidophenyl)-Quinoline-4-Carboxylic Acid Derivatives as Potent SIRT3 Inhibitors - Hui, Qian; Li, Xueming; Fan, Wenli; Gao, Congying; Zhang, Lin; Qin, Hongyu; Wei, Liuya; Zhang, Lei (Frontiers in Chemistry, 2022)
In discovery of novel SIRT3 inhibitors for the treatment of cancer, a series of 2-(4-acrylamidophenyl)-quinoline-4-carboxylic acid derivatives were designed and synthesized. Among the derived compounds, molecule P6 exhibited SIRT3 inhibitory selectivity with IC50 value of 7.2 µM over SIRT1 (32.6 µM) and SIRT2 (33.5 µM). molecular docking analysis revealed a specific binding pattern of P6 in the active site of SIRT3 compared with the bindings in the active site of SIRT1 and SIRT2. In the antiproliferative and colony forming assay, molecule P6 showed potent inhibitory activity against a group of MLLr leukemic cell lines. Further analysis revealed that induction of G0/G1 phase cell cycle arrest and cell differentiation, but not apoptosis, makes contributions to the anticancer effects of P6. Collectively, a potent SIRT3 inhibitor (P6) was discovered as a lead compound for the leukemic differentiation therapy.